SAT0341 Polymyalgia Rheumatica and its Association with Cancer. (9th June 2015) - Pfeifer, E.; Crowson, C.; Major, B.; Matteson, E.
Abstract : Background: Polymyalgia rheumatica (PMR) is a common rheumatologic disease in the elderly population. Several other rheumatologic conditions, including rheumatoid arthritis and systemic lupus erythematosus have been associated with certain forms of cancer. Studies on the relationship between PMR and cancer have yielded mixed results, with one finding up to a 69% increase in the risk of cancer in the first 6 months after diagnosis with PMR while other studies have found no association. These studies have been limited by small sample sizes, limited follow up time and cohort source. Objectives: The purpose of this study is to further investigate if, based on data obtained through the Rochester Epidemiology Project, there is an association between PMR and development of cancer. Methods: A population-based cohort of PMR patients diagnosed between 1/1/1970 and 12/31/1999 was assembled. A comparison cohort of subjects with similar age and sex was also established. Records of the PMR and comparator subjects were reviewed for details concerning diagnosis of cancer. For each malignancy the date of diagnosis, site and type of malignancy were collected. Descriptive statistics were used to summarize the data comparing the PMR and non-PMR cohorts. The cumulative incidence of malignancy in patients with and without PMR, adjusted for the competing risk of death, was estimated and compared using methods by Gray. Cox proportional hazards models were used to assess the trends in malignancy over time. Results: This study included 359 patients diagnosed with PMR and 357 non-PMR subjects. The individuals in these two comparison groups were similar in age (mean age in years ± SD: PMR 73.5±8.5, non-PMR 73.3±8.5), sex (PMR 66.6% female, non-PMR 66.9% female) and follow up time (mean follow up time in years ± SD: PMR 11.8±6.7, non-PMR 10.7±7.4). There was no significant difference in the prevalence of malignancy prior to PMR incidence date/index date between the two groups, with prior malignancies in 41 (11%) of PMR patients and 50 (14%) of non-PMR subjects (p-value 0.31). Analysis of individual solid and hematologic malignancies also revealed no difference between the two groups. Following PMR incidence, evaluation of the cumulative incidence of malignancy at 10 years for PMR patients and non-PMR subjects also showed no difference between the two groups (cumulative incidence at 10 years ± SE: PMR 13.8±2.0, control 13.1±2.0; p-value 0.89). Conclusions: There is no increased risk of malignancy in patients who are diagnosed with PMR when compared to subjects without PMR in this population-based cohort study. Disclosure of Interest: None declared